2022
DOI: 10.3390/metabo12070645
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Metabolite 3-Indolepropionic Acid Mediates Immunosuppression

Abstract: The microbial-derived metabolite, 3-indolepropionic acid (3-IPA), has been intensely studied since its origins were discovered in 2009; however, 3-IPA’s role in immunosuppression has had limited attention. Untargeted metabolomic analyses of T-cell exhaustion and immunosuppression, represented by dysfunctional under-responsive CD8+ T cells, reveal a potential role of 3-IPA in these responses. T-cell exhaustion was examined via infection of two genetically related mouse strains, DBA/1J and DBA/2J, with lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…In a recent study, it was shown to abrogate the pathogenic effect of virus-specific cytotoxic T lymphocytes in certain strains of mice infected with lymphocytic choriomeningitis virus clone 13. 65 The potential role of IPA in other viral infections, notably respiratory infections, remains unclear. This is a relevant question regarding the drop in IPA in HIV-infected people, a phenomenon usually associated with a change in the functional status of the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, it was shown to abrogate the pathogenic effect of virus-specific cytotoxic T lymphocytes in certain strains of mice infected with lymphocytic choriomeningitis virus clone 13. 65 The potential role of IPA in other viral infections, notably respiratory infections, remains unclear. This is a relevant question regarding the drop in IPA in HIV-infected people, a phenomenon usually associated with a change in the functional status of the gut microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Tryptophan can be metabolized into bioactive molecules that function in inflammation and ageing, gut-brain homeostasis, immune regulation, cardiovascular diseases, and endothelial dysfunction (33)(34)(35)(36)(37)(38)(39). It is also implicated in infectious diseases (40,41), including dengue virus infection and disease (10)(11)(12)42).…”
Section: Tryptophan Metabolismmentioning
confidence: 99%
“…IPA was reported to have immunomodulatory, anti-inflammatory and antioxidant effects, and various protective functions in mammals (37,54). IPA abundance has a positive correlation with factors that promote cardiovascular health, and IPA levels decrease in scenarios where cardiovascular health is diminished (55).…”
Section: Tryptophan Metabolismmentioning
confidence: 99%
“…Indeed, 3-IPA has been shown to decrease cell proliferation in breast cancer ( 42 ) and protects against radiation toxicity ( 43 ). The metabolite may also suppress cancer immunity since recent untargeted metabolomic analyses revealed that 3-IPA is elevated in exhausted T cells and was shown to suppress T-cell responses when supplied exogenously ( 44 ). The effects of 3-IPA are proposed to be exerted through pregnane X receptor (PXR) and the aryl hydrocarbon receptor (AHR) ( 42 , 43 ) but the full mechanisms of action remain to be elucidated.…”
Section: Recently Revealed Functional Metabolites With Unknown Mechan...mentioning
confidence: 99%